2018
DOI: 10.1038/s41419-017-0087-3
|View full text |Cite
|
Sign up to set email alerts
|

ZEB1 confers chemotherapeutic resistance to breast cancer by activating ATM

Abstract: Although zinc finger E-box binding homeobox 1 (ZEB1) has been identified as a key factor in the regulation of breast cancer differentiation and metastasis, its potential role in modulating tumor chemoresistance has not been fully understood. Here, through the study of specimens from a large cohort of human breast cancer subjects, we showed that patients with tumors that expressed high levels of ZEB1 responded poorly to chemotherapy. Moreover, ZEB1 expression was positively correlated with expression of B-cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
74
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(77 citation statements)
references
References 62 publications
2
74
0
1
Order By: Relevance
“…No significant influence of RA on the mRNA level was found for the ABCB1, TWIST1 and PTEN genes as compared to the control MCF-7 cells. sion of ZEB1 has been observed in many cancer types and is considered to be associated with poor prognosis in some cancers (breast, ovarian, lung and pancreatic) [18][19][20][21]. The protein encoded by ZEB1 has been identified as the key factor in BC differentiation and metastasis regulation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…No significant influence of RA on the mRNA level was found for the ABCB1, TWIST1 and PTEN genes as compared to the control MCF-7 cells. sion of ZEB1 has been observed in many cancer types and is considered to be associated with poor prognosis in some cancers (breast, ovarian, lung and pancreatic) [18][19][20][21]. The protein encoded by ZEB1 has been identified as the key factor in BC differentiation and metastasis regulation.…”
Section: Resultsmentioning
confidence: 99%
“…The protein encoded by ZEB1 has been identified as the key factor in BC differentiation and metastasis regulation. Patients with various tumors, including breast cancer, demonstrating high ZEB1 expression responded poorly to chemotherapy [21]. In another study, a positive correlation between human telomerase reverse transcriptase (hTERT) and ZEB1 expression in breast cancer was discovered, which indicates that this gene controls cancer cell proliferation and apoptosis [17].…”
Section: Resultsmentioning
confidence: 99%
“…A recent study reported that ZEB1 conferred chemotherapeutic resistance to breast cancer and SLC3A2 is a target gene of ZEB1 in breast cancer chemoresistance [15]. Thus, we investigated the role of SLC3A2 and the interaction between ZEB1 and SLC3A2 in the regulation of cisplatin-resistance in ovarian cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al [15] recently reported that ZEB1 conferred chemotherapeutic resistance in breast cancer and identified that SLC3A2 (CD98hc) was a target gene of ZEB1 in breast cancer chemoresistance, suggesting the possible interaction between ZEB1 and SLC3A2. SLC3A2 is a type II transmembrane cell surface molecule.…”
Section: Introductionmentioning
confidence: 99%
“…ZEB1 is known in the scientific community to play a role in tumorigenicity. Studies have shown that it is also linked to chemoresistance in breast cancer (Zhang 2018). Breast cancer is closely linked to ovarian cancer when considering genetics.…”
Section: Discussionmentioning
confidence: 99%